Combined Effects of Bradyrihizobial Strains, Municipal Solid Waste Compost and Fertilizers on Nodulation, N Content and Uptake of Soybean - Rahman, MM; Sampa, MSA (Journal of Environmental Science and Natural Resources, 2013)
A field experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during January to June 2010 to study the combined effects of Bradyrhizobium, municipal solid waste compost and fertilizers on nodulation, N-content and uptake of soybean. The soil was silty loam in texture having pH 6.94, organic matter 1.62%, total N 0.067%, available P 10.45 ppm, available S 12.00 ppm, exchangeable K 0.08 me/100 g soil and cation exchange capacity 15.00 me/100 g soil. There were eight treatments. The experiment was laid out in a Randomized Complete Block Design with three replications. Phosphorus, potassium and sulphur were applied as basal from TSP, MoP and gypsum respectively. Nitrogen as urea and magnesium as MgCl2 were used for the respective treatments. The seeds were inoculated with the selected bradyrhizobial strains. Compost was prepared from municipal solid waste collected from Mymensingh city. Data on nodulation were recorded at 40 and 60 DAS and the N contents in grain, stover and root were determined. Inoculation of seeds with bradyrhizobial strains and application of MSW compost and fertilizers significantly influenced the parameters studied. Both nodule number and weight irrespective of the treatments progressively increased with time up to 60 DAS. The grain and stover yields due to different treatments ranged from 0.80 t to 1.58 t ha-1 and 8.54 t to 10.75 t ha-1 Bradyrhizobium japonicum strain BAU-101 and application of compost @ 10 t ha-1 DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14799 J. Environ. Sci. & Natural Resources, 5(2): 85-90 2012